Type 1 Plasminogen Deficiency With Pulmonary Involvement: Novel Treatment and Novel Mutation. Issue 4 (May 2021) - Hangul, Melih; Tuzuner, Ahmet B.; Somekh, Ido; Klein, Christoph; Patiroglu, Turkan; Unal, Ekrem; Kose, Mehmet
Abstract : Type 1 plasminogen deficiency is a rare genetic disorder. Type 1 plasminogen deficiency is characterized by fibrin-rich pseudomembrane formation on mucosal surfaces, particularly the conjunctiva. Tracheobronchial tree involvement is a less common reported manifestation of type 1 plasminogen deficiency. Pseudomembranes in the tracheobronchial tree may result in respiratory compromise and ultimately fail if not recognized and treated. Currently, there is no specific replacement therapy approved for the treatment of congenital plasminogen deficiency. In the present paper, we report that type 1 plasminogen deficiency with novel frameshift mutation and pulmonary involvement was treated initially with systemic fresh frozen plasma followed by pulmonary lavage with fresh frozen plasma and tissue plasminogen activator.